2020
DOI: 10.1038/s41598-020-73571-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of real-world early response of DMO to aflibercept therapy to inform future clinical trial design of novel investigational agents

Abstract: New clinical trials for diabetic macular oedema (DMO) are being designed to prove superiority over aflibercept when this agent is already very effective in improving visual acuity (VA) and DMO. The aim of this study was to determine the optimal inclusion–exclusion criteria for trials to aim for superiority in visual outcomes with newer agents. As Phase 1 studies are short duration, we aimed to evaluate the early response of aflibercept in a real-world cohort initiated on monthly aflibercept for 3 consecutive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
3
5
0
Order By: Relevance
“…However, 14.8% of the eyes exhibited a decrease in BCVA of more than five letters. As in previous studies [ 7 , 12 , 13 ], our findings confirm a difference in the response of affected eyes to anti-VEGF treatment. We observed a significant correlation between the number of injections and the anatomical results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, 14.8% of the eyes exhibited a decrease in BCVA of more than five letters. As in previous studies [ 7 , 12 , 13 ], our findings confirm a difference in the response of affected eyes to anti-VEGF treatment. We observed a significant correlation between the number of injections and the anatomical results.…”
Section: Discussionsupporting
confidence: 92%
“…Eyes present with VMT or ERM at baseline are less likely to reach the endpoint of CST < 300 μm. However, the decrease in CST does not reflect the final VA results, nor is it a clear predictor of VA [ 12 , 22 , 23 ]. An analysis of the RIDE and RISE trials revealed that patients with no significant changes in fovea thickness after treatment with anti-VEGF had similar visual acuity and DR improvements to those with immediate retinal thinning [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, 14.8% of the eyes exhibited a decrease in BCVA of more than ve letters. As in previous studies [10], our ndings con rm a difference in the response of affected eyes to anti-VEGF treatment. We observed a signi cant correlation between the number of injections and the anatomical results.…”
Section: Discussionsupporting
confidence: 90%
“…However, the decrease in CST does not re ect the nal VA results, nor is it a clear predictor of VA [19][20][21]. An analysis of the RIDE and RISE trials revealed that patients with no signi cant changes in fovea thickness after treatment with anti-VEGF had similar visual acuity and DR improvements to those with immediate retinal thinning [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, in real-life studies with ranibizumab, eyes with baseline VA less than 37 letters fail to achieve good VA that met driving standards. This outcome was also noted in a study on early response to aflibercept after 3 loading injections in real-life suggesting that there are more eyes with irreversible structural changes in eyes with VA less than 37 letters [ 10 ]. Based on available evidence, early treatment with anti-VEGF agents is recommended.…”
Section: Subjective Factorssupporting
confidence: 55%